Gap free load balancıng ın ıwreless lan networks usıng cell breathıng technıque - Demirci, İlhan (My University, 2014)
Hücre Soluma Yöntemiyle Kablosuz Ağlarda Boşluksuz Yük Dengelemesi Yük dengesinin eşit dağıldığı bir kablosuz alan ağı genellikle erişim noktalarında adaletli kullanıcı dağılımına sahiptir ve bu durum toplam ağ kazancının artırılmasına vesile olur. Fakat, kalabalık bölgelerdeki bazı kullanıcılar, erişim noktalarında adaletsiz yük dağılımına neden olabilir. Bu nedenle kablosuz alan ağı işletmecileri, popüler bölgelerde düzensiz olarak görülen kullanıcı yoğunluğunu dağıtmak için yöntem arayışı içerisindedirler. Mevcut yük dengeleme yöntemleri çoğunlukla kullanıcı ve erişim noktası tarafında, yazılım ve donanım desteğine ihtiyaç duyarlar. Hücre soluma, erişim noktası tarafında uygulanan ve kullanıcı cihazında değişikliğe ihtiyaç duymayan bir sinyal gücü ayarlama yöntemidir. Bu yöntem, bir yük dengeleme mekanizması olarak hücresel ağlarda tanınmış bir kavramdır ve biz bu yöntemi kablosuz yerel alan ağlarına uyguladık. Bu yaklaşım kullanıcılarda ya da haberleşme protokolünde değişikliğe gerek duymamaktadır. Tek değişiklik, erişim noktalarının işaret sinyallerinde gerçekleştirilmiştir ve kullanıcıların servis kalitesini düşürmemek için veri taşıma sinyalinin seviyesinde herhangi bir değişiklik yapılmamıştır. Yoğun erişim noktaları yük yoğunluklarını azaltmak için işaret sinyal seviyelerini düşürebilirler. Fakat, kapsama alanlarının küçültülmesi bazı bölgelere hizmet verilememesine neden olabilir. Sinyal gücü ayarlama yöntemine dayanan Dinamik En Küçük-En Büyük Yük Dengeleme algoritması, kapsama alanlarında oluşabilecek boşlukları devingen şekilde kontrol ederek servis garantisi sunar. Biz, kullanıcı dağılımının heterojen yapısına uygun olarak bu algoritmayı iyileştirdik. Yük seviyelerini baz alarak erişim noktalarının sınıflandırılmasını sağlayan Boşluksuz İstatistiksel En Küçük-En Büyük Yük Dengeleme algoritması, erişim noktalarının kapsama alanlarını etkin şekilde ayarlayabilmek için geliştirilmiştir. Boşluksuz Çevirim içi En Küçük-En Büyük Yük Dengeleme algoritması, en küçük güç seviyesini devingen şekilde atayarak boşluksuz bir servis bölgesi sağlayabilmek için geliştirilmiştir. Kapsamlı bir dizi simülasyon deneyi sonucu, algoritmaların etkili ve adil olduğu gösterilmiştir.

Gap free Load Balancing in Wireless LAN Networks using Cell Breathing Technique A balanced Wireless Local Area Network (WLAN) generally has a fair user distribution among the Access Points (APs) and enables a maximized overall network throughput. However, there are some hotspot areas resulting in uneven load distribution among APs. Hence, WLAN administrators generally deal with the sporadic client congestion in hotspot regions such as popular locations within the network. Existing load balancing techniques mostly require hardware or software contribution at both AP and user side to control the association of users with APs. Cell breathing is a power adjustment technique, which is implemented at AP side and requires no modification at user devices. This technique is a well-known concept in cellular networks as a load balancing mechanism and we applied this technique to the WLAN network. This approach does not require modification to clients or the protocol. The only change is performed at the beacon signal level and the data transmission signal level is not changed in order to avoid degrading client’s performance. Congested APs can reduce their beacon signal levels in order to decrease their load level. However, coverage reduction can create unserviced areas. We provide a dynamic min-max load balancing algorithm based on power adjustment technique, which provides service availability guarantee by dynamically checking the coverage holes. We enhanced the algorithm by increasing awareness to heterogeneous nature of user distribution. We propose Gap-free Statistical Min-Max Priority Load Balancing algorithm, which provides classification for APs by means of their load level, in order to adjust the coverage areas effectively. In addition we propose Gap-free Online Min-Max Priority Load Balancing algorithm in order to provide a gap-free environment by defining the minimum power level assignments dynamically. Our extensive set of simulations showed that our proposed algorithms are effective and fair. ABSTRACT Gap free Load Balancing in Wireless LAN Networks using Cell Breathing Technique A balanced Wireless Local Area Network (WLAN) generally has a fair user distribution among the Access Points (APs) and enables a maximized overall network throughput. However, there are some hotspot areas resulting in uneven load distribution among APs. Hence, WLAN administrators generally deal with the sporadic client congestion in hotspot regions such as popular locations within the network. Existing load balancing techniques mostly require hardware or software contribution at both AP and user side to control the association of users with APs. Cell breathing is a power adjustment technique, which is implemented at AP side and requires no modification at user devices. This technique is a well-known concept in cellular networks as a load balancing mechanism and we applied this technique to the WLAN network. This approach does not require modification to clients or the protocol. The only change is performed at the beacon signal level and the data transmission signal level is not changed in order to avoid degrading client’s performance. Congested APs can reduce their beacon signal levels in order to decrease their load level. However, coverage reduction can create unserviced areas. We provide a dynamic min-max load balancing algorithm based on power adjustment technique, which provides service availability guarantee by dynamically checking the coverage holes. We enhanced the algorithm by increasing awareness to heterogeneous nature of user distribution. We propose Gap-free Statistical Min-Max Priority Load Balancing algorithm, which provides classification for APs by means of their load level, in order to adjust the coverage areas effectively. In addition we propose Gap-free Online Min-Max Priority Load Balancing algorithm in order to provide a gap-free environment by defining the minimum power level assignments dynamically. Our extensive set of simulations showed that our proposed algorithms are effective and fair.
Keywords: Bilgisayar Mühendisliği; Kablosuz Ağlar